2018
DOI: 10.1016/j.jvs.2017.10.063
|View full text |Cite
|
Sign up to set email alerts
|

Sex-based outcomes of lower extremity bypass surgery in hemodialysis patients

Abstract: We found lower use of autogenous conduits in women than in men. In patients who received prosthetic conduit, acute graft failure was higher for women than for men. The benefits of autogenous conduits over prosthetic grafts underscore the need to improve the selection of appropriately sized autogenous conduits for bypass irrespective of gender.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(3 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…Among those who received a prosthetic graft, acute graft failure was higher for females (HR, 1.23 [95% CI, 1.03–1.46]). 76…”
Section: Kidney Diseasementioning
confidence: 99%
“…Among those who received a prosthetic graft, acute graft failure was higher for females (HR, 1.23 [95% CI, 1.03–1.46]). 76…”
Section: Kidney Diseasementioning
confidence: 99%
“…Regarding the overall risk factors for patency loss, we found that bypasses involving limbs with critical limb ischemia, tibial distal targets use of prosthetic grafts and female gender were associated with higher rates of graft failure, which is similar to the existing literature. [13][14][15] We also found that obesity and advanced age were independently associated with less risk of patency loss, factors are not typically associated with graft protection. Focused studies on the effect of age and body habitus are thus avenues for future research within the VQI.…”
Section: Discussionmentioning
confidence: 83%
“…19 In contrast to HD-dependent patients, there were no significant differences in the risk-adjusted outcomes between male and female patients; however, the lower patency and limb salvage noted in black HD patients relative to whites persisted in this study. 28,29 This study is limited in its retrospective design and use of an administrative database. However, data from the USRDS are prospectively collected, are validated, and have been used for peer-reviewed vascular surgery studies in the past.…”
Section: Journal Of Vascular Surgerymentioning
confidence: 99%